Study on Innovation System of Coupling Relations Dynamics in High-speed Trains - ZHANG Weihua (机车电传动)
It was a synergistic, interdependent and interaction relationship between high-speed train and railway, catenaries and airflow. Under high-speed operation conditions, these relations became even stronger, which formed complex coupling dynamics relations. To simulate and experiment the operation service the high-speed train and its coupled sub-systems, the train should be treated as the main focus, with considering various fluid-structure coupled relations between one another, and establishing high-speed train coupled relations innovation architecture were the important quarantee for high-speed train development.